Attitude towards the discipline of physics-chemistry and school achievement: revisiting factor structure to assess gender differences in Portuguese high-school students - Vilia, Paulo (2020)
The importance of attitudes and other variables of the affective domain in education is acknowledged for a long time. In this study, we used an attitude questionnaire to survey 498 Portuguese 9th-grade students to determine the predictive ability of the attitudes towards the discipline of Physics-chemistry on school achievement. Possible gender differences were also investigated after establishing the measurement invariance of the factor structure. The survey instrument presented some issues regarding factor structure. After a new factor analysis using more robust statistical methods, a four-factor structure of attitudes towards Physics-chemistry – Competence to discipline, Pleasure in learning, Anxiety, and Utility – was established and used in this study. The means of the Competence and the Pleasure in learning factors were significantly higher in the boy’s group while the factors Anxiety and Utility were not significantly different between genders. Competence was the most important achievement predictor, with significant positive effects, while the factors Anxiety and, surprisingly, Pleasure in learning presented significant negative impacts on the grades. The possible reasons and consequences for these results are discussed, and some suggestions are made about the importance of considering the relevance of affective variables on teaching and learning high-school Physical sciences.